Ethylene-based polymers with reversible cross-linking agents
By introducing free radical initiator and BiTEMPS methacrylate into ethylene polymers, a crosslinkable polymer composition is formed, which solves the problem that crosslinked polymers cannot be processed and recovered, and realizes the reusability and environmental benefits of the material.
Patent Information
- Application Number
- CN202380052957.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-15
- Filing Date
- 2023-07-14
- Publication Date
- 2025-02-25
AI Technical Summary
Crosslinked ethylene polymers cannot be processed and/or recycled due to the existence of a permanent crosslinking network, resulting in environmental and sustainability problems.
A reprocessable crosslinking composition is formed by dynamic crosslinking reaction using a crosslinkable polymer composition comprising an ethylene polymer, a free radical initiator and 2,2,6,6-tetramethyl-4-piperidyl methacrylate disulfide (BiTEMPS methacrylate).
Reprocessability of ethylene polymers is achieved, allowing fracture and re-formation of cross-linking networks at reprocessing temperatures, thereby re-processing and manufacturing into new products, reducing dependence on natural resources and environmental pollution.
Smart Images

Figure BDA0005235678630000121 
Figure BDA0005235678630000122 
Figure BDA0005235678630000201
Abstract
Description
Background Art
[0001] Crosslinked olefin-based polymers (particularly crosslinked ethylene-based polymers) are well known for their excellent mechanical properties, high thermal stability and outstanding chemical resistance in numerous applications. Unfortunately, crosslinked ethylene-based polymers (also known as thermoset polymers) cannot be reprocessed and / or recycled due to the presence of a permanent crosslink network within the ethylene-based polymer. Therefore, the use of crosslinked ethylene-based polymers is associated with environmental and sustainability issues.
[0002] The ability to reprocess and / or recycle crosslinked ethylene polymers has been a long-standing challenge. Accordingly, the art recognizes a need for crosslinked olefin polymers (particularly crosslinked ethylene polymers) that can be reprocessed and / or recycled. Summary of the invention
[0003] The present disclosure provides a crosslinkable polymer composition. In one embodiment, the crosslinkable polymer composition comprises a vinyl polymer, a free radical initiator, and 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS methacrylate).
[0004] The present disclosure provides a crosslinking composition. In one embodiment, the crosslinking composition comprises an ethylene-based polymer; and 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS methacrylate).
[0005] definition
[0006] All references to the Periodic Table of the Elements herein shall refer to the Periodic Table of the Elements published and copyrighted by CRC Press, Inc. in 2003. Furthermore, any reference to one or more groups shall be to the one or more groups reflected in such Periodic Table of the Elements using the IUPAC system for numbering groups. Unless stated to the contrary, implied by the context, or customary in the art, all parts and percentages are by weight. For purposes of U.S. patent practice, any patent, patent application, or publication referred to herein is incorporated herein by reference in its entirety (or its equivalent U.S. version is so incorporated by reference).
[0007] The numerical range disclosed herein includes all values from the lower limit to the upper limit and including the lower limit and the upper limit. For a range containing clear values (e.g., a range of 1 or 2, or 3 to 5, or 6, or 7), any sub-range between any two clear values is included (e.g., the above range 1 to 7 includes 1 to 2; 2 to 6; 5 to 7; 3 to 7; 5 to 6; etc.).
[0008] Unless stated to the contrary, implicit from the context, or customary in the art, all parts and percentages are by weight and all test methods are current as of the filing date of this disclosure.
[0009] The term "composition" as used herein refers to a mixture of materials which comprise the composition, as well as reaction products and decomposition products formed from the materials of the composition.
[0010] The terms "comprising," "including," "having," and derivatives thereof are not intended to exclude the presence of any additional components, steps, or procedures, whether or not specifically disclosed. For the avoidance of any doubt, all compositions claimed through use of the term "comprising" may include any additional additive, adjuvant, or compound, whether polymeric or otherwise, unless stated to the contrary. In contrast, the term "consisting essentially of excludes from the scope of any subsequent recitation any other components, steps, or procedures, except those that are not essential to operability. The term "consisting of excludes any ingredient, step, or procedure not specifically recited or listed.
[0011] "Ethylene polymers" are polymers containing more than 50 mol% of polymerized ethylene monomers (based on the total amount of polymerizable monomers) and optionally may contain at least one comonomer. Ethylene polymers include ethylene homopolymers and ethylene copolymers (meaning units derived from ethylene and one or more comonomers). The terms "ethylene polymers" and "polyethylene" are used interchangeably. Non-limiting examples of ethylene polymers (polyethylene) include low density polyethylene (LDPE) and linear polyethylene. Non-limiting examples of linear polyethylene include linear low density polyethylene (LLDPE), ultra low density polyethylene (ULDPE), very low density polyethylene (VLDPE), multi-component ethylene copolymers (EPE), ethylene / α-olefin multi-block copolymers (also known as olefin block copolymers (OBC)), substantially linear or linear plastomers / elastomers, and high density polyethylene (HDPE). Generally speaking, polyethylene can be produced in a gas phase fluidized bed reactor, a liquid phase slurry reactor or a liquid phase solution reactor using a heterogeneous catalyst system (such as a Ziegler-Natta catalyst), a homogeneous catalyst system comprising a Group 4 transition metal and a ligand structure (such as a metallocene, a non-metallocene metal center, a heteroaryl, an isovalent aryloxy ether, a phosphinimine, etc.). Combinations of heterogeneous and / or homogeneous catalysts can also be used in a single reactor or dual reactor configuration.
[0012] "Ethylene plastomer / elastomer" is a substantially linear or linear ethylene / α-olefin copolymer containing a homogeneous distribution of short chain branches, which comprises units derived from ethylene and units derived from at least one C3-C 10 The ethylene plastomers / elastomers have a density of 0.870 g / cc to 0.917 g / cc. Non-limiting examples of ethylene plastomers / elastomers include AFFINITY TM Plastomers and elastomers (available from The Dow Chemical Company), EXACT TM Plastomers (available from Exxon Mobil Chemical), Tafmer TM (available from Mitsui), Nexlene TM (available from SK Chemicals Co.) and Lucene TM (Available from LG Chem Ltd.).
[0013] "High density polyethylene" (or "HDPE") is a homopolymer of ethylene or ethylene with at least one C4-C 10 The HDPE may be a unimodal copolymer or a multimodal copolymer. A "unimodal ethylene copolymer" is an ethylene / α-olefin copolymer having one distinct peak in a gel permeation chromatography (GPC) showing a molecular weight distribution. 10 α-olefin copolymers. "Multimodal ethylene copolymers" are ethylene / C4-C6 copolymers having at least two distinct peaks in a GPC graph showing molecular weight distribution. 10 α-olefin copolymers. Multimodal includes copolymers with two peaks (bimodal) and copolymers with more than two peaks. Non-limiting examples of HDPE include DOW TM High-density polyethylene (HDPE) resin (available from The Dow Chemical Company), ELITE TM Enhanced polyethylene resin (available from The Dow Chemical Company), CONTINUUM TM Bimodal polyethylene resin (available from The Dow Chemical Company), LUPOLEN TM(available from LyondellBasell) and HDPE products from Borealis, Ineos and ExxonMobil.
[0014] "Linear low density polyethylene" (or "LLDPE") is a linear ethylene / α-olefin copolymer containing a heterogeneous distribution of short chain branches, which comprises units derived from ethylene and units derived from at least one C3-C 10 Units of α-olefins or C4-C8 α-olefin comonomers. LLDPE is characterized by minimal long chain branching (if any) compared to conventional LDPE. LLDPE has a density of 0.910 g / cc to less than 0.940 g / cc. Non-limiting examples of LLDPE include TUFLIN TM Linear low density polyethylene resin (available from The Dow Chemical Company), DOWLEX TM Polyethylene resin (available from The Dow Chemical Company) and MARLEX TM Polyethylene (available from Chevron Phillips).
[0015] "Low density polyethylene" (or "LDPE") is a homopolymer of ethylene or a polyolefin having a density of 0.915 g / cc to less than 0.940 g / cc. 10 LDPE is composed of ethylene / α-olefin copolymers of C4-C8 α-olefins and contains long chain branches with broad MWD. LDPE is usually produced by high pressure free radical polymerization (tubular reactor or autoclave with free radical initiator). Non-limiting examples of LDPE include MarFlex TM (Chevron Phillips Company), LUPOLEN TM (LyondellBasell) and LDPE products from Borealis, INEOS, ExxonMobil, etc.
[0016] As used herein, "olefin polymer" or "polyolefin" is a polymer containing more than 50 mole % polymerized olefin monomer (based on the total amount of polymerizable monomers) and optionally may contain at least one comonomer. Non-limiting examples of olefin polymers include ethylene polymers and propylene-based polymers.
[0017] "Polymer" is a compound prepared by polymerizing monomers of the same or different types that provide multiple and / or repeating "units" or "monomer units" constituting the polymer in a polymerized form. Therefore, the general term polymer covers the term homopolymer, which is usually used to refer to polymers prepared from only one type of monomer, and the term copolymer, which is usually used to refer to polymers prepared from at least two types of monomers. The general term also covers all forms of copolymers, such as random copolymers, block copolymers, etc. The terms "ethylene / α-olefin polymer" and "propylene / α-olefin polymer" represent copolymers prepared by polymerizing ethylene or propylene and one or more other polymerizable α-olefin monomers, respectively, as described above. It should be noted that although polymers are often referred to as being "made of" one or more specific monomers, "based on" a specific monomer or monomer type, "containing" a specific monomer content, etc., in this context, the term "monomer" should be understood to refer to the polymerized remains of a specific monomer, rather than an unpolymerized species. In general, polymers herein refer to "units" based on the polymerized form of the corresponding monomer.
[0018] Test Method
[0019] Density is measured according to ASTM D792, with results reported in g / cc at 25°C.
[0020] Differential scanning calorimetry (DSC) was performed using a Mettler Toledo DSC822e differential scanning calorimeter to measure the thermal properties of the native polymers and crosslinked compositions (network polymers), including peak and endpoint melting temperatures and crystallinity. The network materials tested for most polymers were the raw synthesized materials prior to compression molding. In the Examples section, polymer 7 (INFUSE TM 9100), thermal property recovery was demonstrated by collecting DSC data after each consecutive compression molding cycle (up to three times) (Table 4). A 10°C / min heating rate and a -40°C / min cooling rate were applied for all measurements in the temperature range of -60°C to 160°C.
[0021] Dynamic Mechanical Analysis (DMA). DMA experiments were performed using a TA Instruments RSA-G2 solid analyzer to measure the storage modulus (E'), loss modulus (E"), and damping ratio (tan δ) of the networks as a function of temperature and recovery under a nitrogen atmosphere. The DMA was operated in tension mode with a frequency of 1 Hz and an oscillating strain of 0.03%. Data were collected from room temperature to 160°C at a heating rate of 3°C / min.
[0022] Thermal creep test. The sample was compression molded into a 0.7 mm thick tensile bar with a bar size of 16 mm x 4.5 mm. The bar was clamped in an oven at 130°C and hung vertically with a 60 g weight hanging from the bottom. The time required for the weight to fall to the bottom of the oven (indicating sample fracture) was measured and tabulated. The standard deviation of three to four creep tests was used to estimate the experimental uncertainty.
[0023] Melt index (MI or I2) (for ethylene-based polymers) is measured according to ASTM D 1238, Condition 190°C / 2.16 kg, where the results are reported in grams per 10 minutes (g / 10 min). 21 Measured according to ASTM D 1238, Condition 190°C / 21.6 kg, and the results are reported in grams per 10 minutes (g / 10 min). DETAILED DESCRIPTION
[0024] The present disclosure provides a crosslinkable polymer composition. In one embodiment, the crosslinkable polymer composition comprises a vinyl polymer, a free radical initiator, and 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS methacrylate).
[0025] A. Ethylene polymers
[0026] The crosslinkable polymer composition comprises an ethylene polymer. The ethylene polymer can be an ethylene homopolymer, an ethylene / C3-C 10 Alpha-olefin copolymers or ethylene C4-C8 alpha-olefin copolymers. The melt index (MI) of the ethylene polymer is 0.1g / 10min to 100g / 10min, or 1g / 10min to 100g / 10min, or 1g / 10min to 50g / 10min, or 1g / 10min to 25g / 10min, or 1g / 10min to 10g / 10min, or 1g / 10min to 5g / 10min. Non-limiting examples of suitable ethylene polymers include ethylene plastomers / elastomers, high-density polyethylene (HDPE), linear low-density polyethylene (LLDPE), low-density polyethylene (LDPE), ethylene / alpha-olefin multi-block copolymers, and combinations thereof.
[0027] In one embodiment, the ethylene-based polymer is an ethylene plastomer / elastomer.
[0028] In one embodiment, the ethylene-based polymer is HDPE.
[0029] In one embodiment, the ethylene-based polymer is LLDPE.
[0030] In one embodiment, the ethylene-based polymer is LDPE.
[0031] In one embodiment, the ethylene polymer is an ethylene / α-olefin multi-block copolymer. The term "ethylene / α-olefin multi-block copolymer" refers to an ethylene / C4-C8 α-olefin multi-block copolymer composed of ethylene and a copolymerizable C4-C8 α-olefin comonomer (and optional additives) in polymerized form, the polymer being characterized in that multiple blocks or segments of two polymerized monomer units are different in chemical or physical properties, and the blocks are connected (or covalently bonded) in a linear manner, i.e., a polymer containing chemically distinguishable units connected end-to-end relative to the polymerized olefinic functionality. Ethylene / α-olefin multi-block copolymers include block copolymers having two blocks (diblocks) and more than two blocks (multi-blocks). C4-C8 α-olefins are selected from butene, hexene and octene. Ethylene / α-olefin multi-block copolymers do not contain or otherwise do not contain styrene (i.e., do not contain styrene), and / or ethylene aromatic monomers, and / or conjugated dienes. When referring to the amount of "ethylene" or "comonomer" in a copolymer, it is understood that this refers to polymerized units thereof. In some embodiments, the ethylene / α-olefin multi-block copolymer may be represented by the formula: (AB) n ; wherein n is at least 1, preferably an integer greater than 1, such as 2, 3, 4, 5, 10, 15, 20, 30, 40, 50, 60, 70, 80, 90, 100 or more, "A" represents a hard block or segment and "B" represents a soft block or segment. Preferably, A and B are connected or covalently bonded in a substantially linear manner, or in a linear manner, relative to a substantially branched or substantially star-shaped manner. In other embodiments, the A blocks and B blocks are randomly distributed along the polymer chain. In other words, the block copolymer generally does not have the following structure: AAA-AA-BBB-BB. In one embodiment, the ethylene / α-olefin multi-block copolymer does not have a third type of block, which comprises one or more different comonomers. In another embodiment, block A and block B each have monomers or comonomers that are substantially randomly distributed within the block. In other words, neither block A nor block B comprises two or more subsegments (or subblocks) of different compositions, such as an end segment having a substantially different composition than the remainder of the block.
[0032] In one embodiment, ethylene comprises most of the mole fraction of the entire ethylene / α-olefin multi-block copolymer, i.e., ethylene comprises at least 50% by weight of the entire ethylene / α-olefin multi-block copolymer. More preferably, ethylene comprises at least 60% by weight, at least 70% by weight, or at least 80% by weight, and the substantial remainder of the entire ethylene / α-olefin multi-block copolymer comprises C4-C8 α-olefin comonomers. In one embodiment, the ethylene / α-olefin multi-block copolymer contains 50% to 90% by weight of ethylene, or 60% to 85% by weight of ethylene, or 65% to 80% by weight of ethylene. For a variety of ethylene / octene multi-block copolymers, the composition comprises an ethylene content greater than 80% by weight of the entire ethylene / octene multi-block copolymer and an octene content of 10% to 15% by weight, or 15% to 20% by weight of the entire multi-block copolymer.
[0033] Ethylene / alpha-olefin multi-block copolymers include various amounts of "hard" segments and "soft" segments. "Hard" segments are blocks of polymerized units, wherein based on the weight of the polymer, ethylene is present in an amount greater than 90 wt %, or 95 wt %, or greater than 95 wt %, or greater than 98 wt %, up to 100 wt %. In other words, by the weight of the polymer, the comonomer content (except the monomer content of ethylene) in the hard segments is less than 10 wt %, or 5 wt %, or less than 5 wt %, or less than 2 wt %, and can be as low as zero. In some embodiments, the hard segments include all or substantially all units derived from ethylene. "Soft" segments are blocks of polymerized units, in which, by the weight of the polymer, the comonomer content (the content of monomers other than ethylene) is greater than 5 wt %, or greater than 8 wt %, greater than 10 wt %, or greater than 15 wt %. In one embodiment, the comonomer content in the soft segments is greater than 20 wt%, greater than 25 wt%, greater than 30 wt%, greater than 35 wt%, greater than 40 wt%, greater than 45 wt%, greater than 50 wt%, or greater than 60 wt% and can be as high as 100 wt%.
[0034] The soft segment can be present in ethylene / alpha-olefin multi-block copolymers from 1% to 99% by weight of the total weight of the ethylene / alpha-olefin multi-block copolymer, or from 5% to 95% by weight, 10% to 90% by weight, 15% to 85% by weight, 20% to 80% by weight, 25% to 75% by weight, 30% to 70% by weight, 35% to 65% by weight, 40% to 60% by weight, or 45% to 55% by weight of the total weight of the ethylene / alpha-olefin multi-block copolymer. On the contrary, the hard segment can be present in a similar range. The soft segment weight percentage and the hard segment weight percentage can be calculated based on the data obtained from DSC or NMR. Such methods and calculations are disclosed in, for example, USP 7,608,668, entitled "Ethylene / α-Olefin Block Inter-Polymers", filed on March 15, 2006 in the name of Colin L.P. Shan, Lonnie Hazlitt et al. and assigned to Dow Global Technologies Inc., the disclosure of which is incorporated herein by reference in its entirety. Specifically, the hard segment weight percentage and the soft segment weight percentage and the comonomer content can be determined as described in columns 57 to 63 of USP 7,608,668.
[0035] The ethylene / α-olefin multi-block copolymer comprises two or more chemically distinct regions or segments (referred to as "blocks") that are linked (or covalently bonded) in a linear manner, i.e., they contain chemically distinguishable units that are linked end-to-end with respect to the polymerized olefinic functionality, rather than in a pendant or grafted manner. In one embodiment, the blocks differ in the amount or type of comonomer incorporated, density, amount of crystallinity, crystallite size attributable to polymers of such compositions, type or degree of stereoisomerism (isotactic or syndiotactic), regioregularity or regioirregularity, amount of branching (including long chain branching or hyperbranching), uniformity, or any other chemical or physical characteristic. Compared to prior art block interpolymers, including those produced by sequential monomer addition, stereolabile catalysts, or anionic polymerization techniques, the inventive ethylene / α-olefin multi-block copolymers are characterized by a unique distribution of polymer polydispersity (PDI or Mw / Mn or MWD), polydisperse block length distribution, and / or polydisperse block number distribution, which, in one embodiment, is due to the effect of one or more shuttling agents in combination with various catalysts used in their preparation.
[0036] In one embodiment, the ethylene / α-olefin multi-block copolymer is produced in a continuous process and has a polydispersity index (Mw / Mn) of 1.7 to 3.5, or 1.8 to 3, or 1.8 to 2.5, or 1.8 to 2.2. When prepared in a batch or semi-batch process, the ethylene / α-olefin multi-block copolymer has a Mw / Mn of 1.0 to 3.5, or 1.3 to 3, or 1.4 to 2.5, or 1.4 to 2.
[0037] In addition, the ethylene / α-olefin multi-block copolymer has a PDI (or Mw / Mn) that fits the Schultz-Flory distribution rather than the Poisson distribution. The ethylene / α-olefin multi-block copolymer of the present invention has both a polydisperse block distribution and a polydisperse distribution of block sizes. This results in the formation of a polymer product with improved and distinguishable physical properties. The theoretical benefits of a polydisperse block distribution have been previously described in Potemkin, Physical Review E( Physical Review ) (1998) 57(6), pp. 6902-6912 and Dobrynin, Journal of Chemical Physics ( J.Chem.Phvs.)》 The theoretical benefits of polydisperse block distributions are modeled and discussed in (1997) 107(21), pp. 9234-9238.
[0038] In one embodiment, the ethylene / α-olefin multi-block copolymers of the present invention have a most probable distribution of block lengths.
[0039] In another embodiment, the ethylene / α-olefin multi-block copolymers of the present disclosure, especially those copolymers made in a continuous solution polymerization reactor, have the most probable distribution of block lengths. In one embodiment of the present disclosure, the ethylene / α-olefin multi-block copolymers are defined as having:
[0040] (A) an Mw / Mn of about 1.7 to about 3.5, at least one melting point Tm in degrees Celsius and a
[0041] / density d in cubic centimeters, where the values of Tm and d correspond to the following relationship:
[0042] Tm>-2002.9+4538.5(d)-2422.2(d) 2 , and / or
[0043] (B) an Mw / Mn of from about 1.7 to about 3.5, and is characterized by a heat of fusion, DH, in J / g, and a differential, DT, in degrees Celsius, defined as the temperature difference between the tallest DSC peak and the tallest Crystallization Analysis Separation ("CRYSTAF") peak, wherein the numerical values of DT and DH have the following relationship:
[0044] For DH greater than zero and up to 130 J / g, DT>-0.1299DH+62.81
[0046] For DH greater than 130 J / g, DT ≥ 48 °C
[0047] wherein at least 5% of the cumulative polymer is used to determine the CRYSTAF peak, and if less than 5% of the polymer has an identifiable CRYSTAF peak, then the CRYSTAF temperature is 30°C; and / or
[0048] (C) an elastic recovery Re in percent measured at 300% stress and 1 cycle with a compression molded ethylene / α-olefin interpolymer film, and a density d in grams per cubic centimeter, wherein when the ethylene / α-olefin interpolymer is substantially free of a crosslinked phase, the values of Re and d satisfy the following relationship:
[0049] Re>1481–1629(d); and / or
[0050] (D) having a molecular fraction eluting between 40°C and 130°C when fractionated using TREF, characterized in that said fraction has a molar comonomer content at least 5% higher than that of an equivalent comparable random ethylene interpolymer fraction eluting between the same temperatures, wherein said comparable random ethylene interpolymer has the same comonomers and has a molar comonomer content of at least 5% higher than that of an equivalent comparable random ethylene interpolymer fraction eluting between the same temperatures
[0051] Melt index, density and molar comonomer content (based on the total polymer) within 10% of an interpolymer of olefins containing olefins having a molecular weight of 0.1477 W / α-olefins; and / or
[0052] (E) has a storage modulus G'(25°C) at 25°C and a storage modulus G' at 100°C
[0053] (100°C), wherein the ratio of G'(25°C) to G'(100°C) is in the range of 1:1 to 9:1.
[0054] The ethylene / α-olefin multi-block copolymer may also have:
[0055] (F) a molecular fraction eluting between 40°C and 130°C when fractionated using TREF, characterized in that the block index of the fraction is at least 0.5 and at most 1, and the molecular weight distribution Mw / Mn is greater than 1.3; and / or
[0056] (G) The average block index is greater than zero and at most 1.0, and the molecular weight distribution Mw / Mn is greater than 1.3.
[0057] It should be understood that the ethylene / α-olefin multi-block copolymer may have one, some, all or any combination of properties (A)-(G). The block index may be determined as described in detail in USP 7,608,668, which is incorporated herein by reference for the purpose. Analytical methods for determining properties (A) to (G) are disclosed, for example, in USP 7,608,668, column 31, line 26 to column 35, line 44, which is incorporated herein by reference for the purpose.
[0058] In one embodiment, the ethylene / α-olefin multi-block copolymer has hard segments and soft segments, is free of styrene, consists solely of (i) ethylene and (ii) C4-C8 α-olefins or C8 α-olefins (and optional additives), and is defined as having an Mw / Mn of 1.7 to 3.5, at least one melting point Tm in degrees Celsius, and a density d in grams / cubic centimeter, wherein the numerical values of Tm and d correspond to the following relationship:
[0059] Tm>-2002.9+4538.5(d)-2422.2(d) 2 ,
[0060] wherein the density d is 0.850 g / cc, or 0.860 g / cc, or 0.870 g / cc to 0.875 g / cc, or 0.877 g / cc, or 0.880 g / cc, or 0.890 g / cc; and the melting point Tm is 110°C, or 115°C, or 120°C to 125°C, or 130°C, or 135°C.
[0061] In one embodiment, the ethylene / α-olefin multi-block copolymer is an ethylene / 1-octene multi-block copolymer (consisting only of ethylene and octene comonomers) and has one, some or all of the following characteristics:
[0062] (i) an Mw / Mn of from 1.7, or 1.8 to 2.2, or 2.5, or 3.5; and / or
[0063] (ii) a density of 0.860 g / cc, or 0.865 g / cc to 0.870 g / cc, or 0.877 g / cc, or 0.880 g / cc; and / or
[0064] (iii) a melting point Tm of 115°C, or 118°C, or 119°C, or 120°C to 120°C, or 123°C, or 125°C; and / or
[0065] (iv) a melt index (MI) of 0.1 g / 10 min, or 0.5 g / 10 min to 1.0 g / 10 min, or 2.0 g / 10 min, or 5 g / 10 min, or 10 g / 10 min; and / or
[0066] (v) 50 to 85 weight percent soft segments and 40 to 15 weight percent hard segments (based on the total weight of the ethylene / octene multi-block copolymer); and / or
[0067] (vi) 10 mol%, or 13 mol%, or 14 mol%, or 15 mol% to 16 mol%, or 17 mol%, or 18 mol%, or 19 mol%, or 20 mol% octene in the soft segment; and / or
[0068] (vii) 0.5 mol%, or 1.0 mol%, or 2.0 mol%, or 3.0 mol% to 4.0 mol%, or 5 mol%, or 6 mol%, or 7 mol%, or 9 mol% of octene in the hard segments; and / or
[0069] (viii) 300% min at 21°C as measured according to ASTM D 1708 ·1 50%, or 60% to 70%, or 80%, or 90% elastic recovery (Re) at deformation rate; and / or
[0070] (ix) Polydispersity distribution of blocks and polydispersity distribution of block sizes (hereinafter referred to as multi-block copolymer properties (i) to (ix)).
[0071] In one embodiment, the ethylene / α-olefin multi-block copolymer is an ethylene / octene multi-block copolymer. The ethylene / octene multi-block copolymer is marketed under the trade name INFUSE TM Sold and available from The Dow Chemical Company, Midland, Michigan, USA.
[0072] Ethylene / α-olefin multi-block copolymers can be produced via a chain shuttling process as described in USP 7,858,706, which is incorporated herein by reference. Specifically, suitable chain shuttling agents and related information are listed in column 16, line 39 to column 19, line 44. Suitable catalysts are described in column 19, line 45 to column 46, line 19 and suitable co-catalysts are described in column 46, line 20 to column 51, line 28. The process is described throughout the literature, but especially in column 51, line 29 to column 54, line 56. The process is also described, for example, in the following: USP 7,608,668; USP 7,893,166; and USP 7,947,793.
[0073] The ethylene / α-olefin multi-block copolymer may include more than one ethylene / α-olefin multi-block copolymer.
[0074] B. Free Radical Initiators
[0075] The crosslinkable composition comprises a free radical initiator. In one embodiment, the free radical initiator is an organic peroxide. Non-limiting examples of suitable organic peroxides include bis(1,1-dimethylethyl)peroxide; bis(1,1-dimethylpropyl)peroxide; 2,5-dimethyl-2,5-bis(1,1-dimethylethylperoxy)hexane; 2,5-dimethyl-2,5-bis(1,1-dimethylethylperoxy)hexyne; 4,4-bis(1,1-dimethylethylperoxy)pentanoic acid; butyl ester; 1,1-bis(1,1-dimethylethylperoxy)-3,3,5-trimethylcyclohexane; benzoyl peroxide; tert-butyl peroxybenzoate; di-tert-amyl peroxide ( "DTAP"); bis(α-tert-butylperoxyisopropyl)benzene ("BIPB"); isopropylcumyl tert-butyl peroxide; tert-butylcumyl peroxide; di-tert-butyl peroxide; 2,5-bis(tert-butylperoxy)-2,5-dimethylhexane; 2,5-bis(tert-butylperoxy)-2,5-dimethylhexyne-3,1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane; isopropylcumylcumyl peroxide; butyl 4,4-di(tert-butylperoxy)valerate; di(isopropylcumyl) peroxide; diisopropylbenzene peroxide, and combinations thereof.
[0076] In one embodiment, the free radical initiator is dicumyl peroxide.
[0077] C. BiTEMPS methacrylate disulfide
[0078] The crosslinkable polymer composition comprises 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide, interchangeably referred to as "BiTEMPS methacrylate" or "BiTEMPS" or "BiT." BiTEMPS methacrylate disulfide has the following structure 1.
[0079] Structure 1
[0080]
[0081] In one embodiment, the crosslinkable polymer composition comprises:
[0082] 70 wt % to 98.5 wt %, or 77 wt % to 98.5 wt % of an ethylene polymer;
[0083] 0.5 to 10 wt%, or 0.5 to 5 wt%, 0.5 to 3.0 wt%, or 0.5 to 1.5 wt%, or 1.5 to 3.0 wt% of a free radical initiator which is an organic peroxide (e.g., dicumyl peroxide); and
[0084] 1 wt % to 20 wt %, or 1 wt % to 15 wt %, or 3 wt % to 20 wt %, or 3 wt % to 10 wt % BiTEMPS methacrylate disulfide. It is understood that the aggregate of the vinyl polymer, free radical initiator, and BiTEMPS methacrylate disulfide (and optional additives) totals 100 wt % of the crosslinkable polymer composition.
[0085] The present disclosure provides a cross-linked composition. The cross-linkable polymer composition is melt blended at a temperature of 100°C to 250°C, or 120°C to 200°C, or 120°C to 180°C, or 120°C to 160°C to initiate a cross-linking reaction and form a cross-linked composition. In one embodiment, the cross-linked composition comprises an ethylene polymer and 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS methacrylate). The cross-linked composition contains a disulfide bond formed by BiTEMPS methacrylate through a cross-linking reaction, and the disulfide bond has the following structure 2.
[0086] Structure 2
[0087]
[0088] The term (and structure) "P" in Structure 2 above refers to the chains of polymerized ethylene (and optional comonomers) of the ethylene polymer. The ethylene polymer of the crosslinked composition can be any ethylene polymer having a MI of 0.1 g / 10 min to 100 g / 10 min as previously disclosed herein. Non-limiting examples of suitable ethylene polymers include ethylene plastomers / elastomers, high density polyethylene (HDPE), linear low density polyethylene (LLDPE), low density polyethylene (LDPE), ethylene / α-olefin multi-block copolymers, and combinations thereof.
[0089] In one embodiment, the ethylene polymer is a virgin ethylene polymer. As used herein, a "virgin ethylene polymer" is an ethylene polymer that has not been subjected to a crosslinking reaction. In other words, the term "virgin ethylene polymer" refers to the ethylene polymer that was present in the crosslinked composition before the ethylene polymer was crosslinked with the BiTEMPS methacrylate. The virgin ethylene polymer is the ethylene polymer before crosslinking, and the crosslinked composition comprises the same ethylene polymer that is virgin but now crosslinked with the BiTEMPS methacrylate. In this way, the virgin ethylene polymer is used as a benchmark for evaluating the performance of the crosslinked composition. The crosslinked composition has
[0090] (i) a storage modulus value E' at 140°C that is greater than the storage modulus value E' of the native ethylene polymer at 140°C;
[0091] (ii) a tan δ value at 60°C that is less than the tan δ value of the virgin ethylene polymer at 60°C;
[0092] and
[0093] (iii) a tan δ value at 140°C that is less than the tan δ value of the native ethylene polymer at 140°C.
[0094] In one embodiment, the crosslinked composition comprises 80 wt % to 97 wt % of the ethylene polymer and 3 wt % to 20 wt % of the BiTEMPS methacrylate, the aggregate of the ethylene polymer and the BiTEMPS methacrylate (and optional additives) totaling 100 wt % of the crosslinked composition. The crosslinked composition has
[0095] (i) a storage modulus value E' greater than 1 MPa at 60°C;
[0096] (ii) a storage modulus value E' greater than 0.1 MPa at 140°C;
[0097] (iii) a tan delta value of less than 0.17 at 60°C; and
[0098] (iv) a tan δ value of less than 0.62 at 140°C.
[0099] D. Blend Components
[0100] In one embodiment, the crosslinkable composition and / or the crosslinked composition comprises a blend component. Non-limiting examples of suitable blend components include ethylene-vinyl acetate (EVA), polyolefins (e.g., polyethylene other than ethylene polymers crosslinked with BiTEMPS methacrylate and polypropylene), polymers (e.g., polystyrene, ABS, SBS, etc.), and combinations thereof. Non-limiting examples of suitable polyolefins include polyethylene; polypropylene; polybutene (e.g., polybutene-1); polypentene-1; polyhexene-1; polyoctene-1; polydecene-1; poly-3-methylbutene-1; poly-4-methylpentene-1; polyisoprene; polybutadiene; poly-1,5-hexadiene; interpolymers derived from olefins; interpolymers derived from olefins and other polymers such as polyvinyl chloride, polystyrene, polyurethane, etc.; and mixtures thereof.
[0101] In one embodiment, the polyolefin is a homopolymer such as polyethylene, polypropylene, polybutene, polypentene-1, poly-3-methylbutene-1, poly-4-methylpentene-1, polyisoprene, polybutadiene, poly-1,5-hexadiene, polyhexene-1, polyoctene-1, and polydecene-1.
[0102] Non-limiting examples of polyethylenes suitable as blend components (other than ethylene polymers crosslinked with BITEMPS methacrylate) include ultra low density polyethylene (ULDPE), linear low density polyethylene (LLDPE), low density polyethylene (LDPE), medium density polyethylene (MDPE), high density polyethylene (HDPE), high molecular weight high density polyethylene (HMW-HDPE), ultra high molecular weight polyethylene (UHMW-PE), and combinations thereof. Non-limiting examples of polypropylenes include low density polypropylene (LDPP), high density polypropylene (HDPP), high melt strength polypropylene (HMS-PP), and combinations thereof. In one embodiment, the blend component is high melt strength polypropylene (HMS-PP), low density polyethylene (LDPE), or combinations thereof.
[0103] E. Additives
[0104] The crosslinkable composition and / or crosslinked composition may contain one or more optional additives. Non-limiting examples of suitable additives include grafting initiators, crosslinking catalysts, blowing agents, blowing agent activators (e.g., zinc oxide, zinc stearate, etc.), auxiliary agents (e.g., triallyl cyanurate), plasticizers, processing oils, processing aids, carbon black, colorants or pigments, stability control agents, nucleating agents, fillers, antioxidants, acid scavengers, ultraviolet (UV) stabilizers, flame retardants, lubricants, processing aids, extrusion aids, and combinations thereof. When present, the total amount of additives may be greater than 0% to 80%, or 0.001% to 70%, or 0.01% to 60%, or 0.1% to 50%, or 0.1% to 40%, or 0.1% to 20%, or 0.1% to 10%, or 0.1% to 5% of the total weight of the composition.
[0105] In one embodiment, the crosslinkable composition and / or the crosslinked composition comprises an antioxidant. Non-limiting examples of suitable antioxidants include aromatic amines or hindered amines, such as alkyl diphenylamines, phenyl-α-naphthylamines, alkyl or aralkyl substituted phenyl-α-naphthylamines, alkylated p-phenylenediamines, tetramethyl diamino diphenylamine, etc.; phenols such as 2,6-di-tert-butyl-4-methylphenol; 1,3,5-trimethyl-2,4,6-tris (3',5,-di-tert-butyl-4-hydroxybenzyl) benzene; tetrakis [(methylene (3,5-di-tert-butyl-4-hydroxyhydrocinnamate)] methane (e.g., IRGANOX TM 1010, available from Ciba Geigy, New York); acryloyl-modified phenol; octadecyl 3,5-di-tert-butyl-4-hydroxycinnamate (e.g., IRGANOX TM 1076, commercially available from Ciba Geigy); phosphites and phosphonites; hydroxylamines; benzofuranone derivatives; and combinations thereof. When used, the amount of antioxidant in the composition can be from greater than 0% to 5% by weight, or from 0.0001% to 2.5% by weight, or from 0.001% to 1% by weight, or from 0.001% to 0.5% by weight of the total weight of the composition.
[0106] In one embodiment, the crosslinkable composition and / or the crosslinked composition comprises a UV stabilizer. Non-limiting examples of suitable UV stabilizers include benzophenones, benzotriazoles, aryl esters, oxanilides, acrylates, formamidines, carbon black, hindered amines, nickel quenchers, hindered amines, phenolic antioxidants, metal salts, zinc compounds, and combinations thereof. When used, the amount of the UV stabilizer may be greater than 0% to 5% by weight, or 0.01% to 3% by weight, or 0.1% to 2% by weight, or 0.1% to 1% by weight of the total weight of the composition.
[0107] In one embodiment, the crosslinkable composition and / or the crosslinked composition include a colorant or pigment. The non-limiting example of suitable colorants or pigments includes inorganic pigments, for example, metal oxides such as iron oxide, zinc oxide and titanium dioxide, mixed metal oxides, carbon black, organic pigments such as anthraquinone, anthraquinone, azo and monoazo compounds, arylamide, benzimidazolone, BONA lake, diketopyrrolopyrrole, dioxazine, disazo compounds, diarylide compounds, flavanone, indanthrone, isoindolinone, isoindolinone, metal complex, monoazo salt, naphthol, b-naphthol, naphthol AS, naphthol lake, perylene, perylone, phthalocyanine, pyranthrone, quinacridone and quinophthalone, and combinations thereof. When used, the amount of colorant or pigment in the composition can be greater than 0% by weight to 10% by weight, or 0.1% by weight to 5% by weight, or 0.25% by weight to 2% by weight of the total weight of the composition.
[0108] In one embodiment, the crosslinkable composition and / or the crosslinked composition comprises a filler. Non-limiting examples of suitable fillers include talc, calcium carbonate, chalk, calcium sulfate, clay, kaolin, silica, glass, fumed silica, mica, wollastonite, feldspar, aluminum silicate, calcium silicate, aluminum oxide, hydrated aluminum oxide such as aluminum oxide trihydrate, glass microspheres, ceramic microspheres, thermoplastic microspheres, barite, wood flour, glass fiber, carbon fiber, marble powder, cement powder, magnesium oxide, magnesium hydroxide, antimony oxide, zinc oxide, barium sulfate, titanium dioxide, titanates, and combinations thereof.
[0109] In one embodiment, the filler is barium sulfate, talc, calcium carbonate, silicon dioxide, glass, glass fiber, aluminum oxide, titanium dioxide or a mixture thereof. In another embodiment, the filler is talc, calcium carbonate, barium sulfate, glass fiber or a mixture thereof. When used, the amount of filler in the composition can be greater than 0% to 80% by weight, or 0.1% to 60% by weight, or 0.5% to 40% by weight, or 1% to 30% by weight, or 10% to 40% by weight of the total weight of the composition.
[0110] In one embodiment, the crosslinkable composition and / or the crosslinked composition comprises a lubricant. Non-limiting examples of suitable lubricants include fatty alcohols and dicarboxylic acid esters thereof, fatty acid esters of short-chain alcohols, fatty acids, fatty acid amides, metal soaps, oligomeric fatty acid esters, fatty acid esters of long-chain alcohols, montan wax, polyethylene wax, polypropylene wax, natural and synthetic paraffin waxes, fluoropolymers, and combinations thereof. When used, the amount of lubricant in the composition may be greater than 0% to 5% by weight, or 0.1% to 4% by weight, or 0.1% to 3% by weight of the total weight of the composition.
[0111] In one embodiment, the crosslinkable composition and / or the crosslinked composition include an antistatic agent. Non-limiting examples of suitable antistatic agents include conductive fillers (e.g., carbon black, metal particles and other conductive particles), fatty acid esters (e.g., glyceryl monostearate), ethoxylated alkylamines, diethanolamine, ethoxylated alcohols, alkyl sulfonates, alkyl phosphates, quaternary ammonium salts, alkyl betaines, and combinations thereof. When used, the amount of the antistatic agent in the composition may be greater than 0% to 5% by weight, or 0.01% to 3% by weight, or 0.1% to 2% by weight of the total weight of the composition.
[0112] In one embodiment, the crosslinkable composition and / or the crosslinked composition include a blowing agent. "Blowing agent" is a substance that can produce a porous structure in the composition by a foaming process. The blowing agent is used to foam the crosslinked composition. Non-limiting examples of suitable blowing agents include inorganic physical blowing agents such as air, argon, nitrogen, carbon dioxide, argon, helium, oxygen and neon, and organic physical blowing agents, such as aliphatic hydrocarbons, such as propane, n-butane, isobutane, n-pentane, isopentane and n-hexane; alicyclic hydrocarbons, such as cyclohexane and cyclopentane; halogenated hydrocarbons, such as chlorofluoromethane, trifluoromethane, 1,1-difluoroethane, 1,1,1,2-tetrafluoroethane, methyl chloride, ethyl chloride and dichloromethane; and dialkyl ethers, such as dimethyl ether, diethyl ether and methyl ethyl ether.
[0113] The limiting examples of suitable organic blowing agents include aliphatic hydrocarbons with 1-6 carbon atoms, aliphatic alcohols with 1-3 carbon atoms, and fully and partially halogenated aliphatic hydrocarbons with 1-4 carbon atoms. The limiting examples of suitable aliphatic hydrocarbons include methane, ethane, propane, n-butane, isobutane, n-pentane, isopentane, neopentane, etc. The limiting examples of suitable aliphatic alcohols include methanol, ethanol, n-propyl alcohol, and isopropyl alcohol. The limiting examples of suitable fully and partially halogenated aliphatic hydrocarbons include fluorocarbons, chlorocarbons, and chlorofluoro compounds. Non-limiting examples of suitable fluorocarbons include methyl fluoride, perfluoromethane, ethyl fluoride, 1,1-difluoroethane (HFC152a), 1,1,1-trifluoroethane (HFC-143a), 1,1,1,2-tetrafluoroethane (HFC-134a), pentafluoroethane, difluoromethane, perfluoroethane, 2,2-difluoropropane, 1,1,1-trifluoropropane, perfluoropropane, dichloropropane, difluoropropane, perfluorobutane, and perfluorocyclobutane. Non-limiting examples of suitable partially halogenated chlorocarbons and chlorofluoro compounds include methyl chloride, methylene chloride, ethyl chloride, 1,1,1-trichloroethane, 1,1-dichloro-1-fluoroethane (HCFC-141b), 1-chloro-1,1-difluoroethane (HCFC-142b), 1,1-dichloro-2,2,2-trifluoroethane (HCFC-123), and 1-chloro-1,2,2,2-tetrafluoroethane (HCFC-124). Non-limiting examples of suitable fully halogenated chlorofluoro compounds include trichloromonofluoromethane (OPOI 1), dichlorodifluoromethane (CFO-12), trichlorotrifluoroethane (CFO-113), 1,1,1-trifluoroethane, pentafluoroethane, dichlorotetrafluoroethane (CFO-114), chloroheptafluoropropane, and dichlorohexafluoropropane. Non-limiting examples of suitable chemical blowing agents include azodicarbonamide, azobisisobutyronitrile, benzenesulfonylhydrazide, 4,4-hydroxybenzenesulfonylsemicarbazide, p-toluenesulfonylsemicarbazide, barium azodicarboxylate, N,N'-dimethyl-N,N'-dinitrosoterephthalamide, and trihydrazinotriazine.
[0114] BiTEMPS methacrylate is a "dynamic crosslinker". The dynamic crosslinker BiTEMPS methacrylate enables the formation of a crosslinked network with ethylene polymers through disulfide bonds between the chains of the ethylene polymers (in the presence of a free radical initiator), thereby forming a crosslinked ethylene polymer composition. The crosslinking is dynamic because the disulfide bonds can be broken when the crosslinked ethylene polymer composition is subjected to a "reprocessing temperature", thereby allowing the chains to move and exchange, which is a temperature of 120°C to 160°C, or 130°C to 160°C. At the reprocessing temperature, the disulfide bonds in the crosslinked ethylene polymer composition are broken to form a reprocessable ethylene polymer composition. The reprocessable ethylene composition is cooled to below the reprocessing temperature to form a re-crosslinked ethylene polymer composition.
[0115] The dynamic crosslinker BiTEMPS methacrylate enables cyclic "reprocessing" to make new polymer articles. When the crosslinked ethylene polymer composition is heated to the reprocessing temperature, the disulfide bonds are broken or otherwise cleaved, allowing the previously crosslinked ethylene polymer composition to flow at the reprocessing temperature, thereby forming a "reprocessable ethylene polymer composition". Heating to the reprocessing temperature enables chain scission and polymer chain flow, thereby allowing the ethylene composition to be easily reshaped. At the reprocessing temperature, the reprocessable ethylene polymer composition is no longer crosslinked, but is flowable, allowing the now flowable, reprocessable ethylene composition (with BiTEMPS methacrylate) to be shaped and / or manufactured into a new preform or article. When cooled to below the "reprocessing temperature", the disulfide bonds are formed again, the network is reestablished, and the re-crosslinked ethylene composition is formed in a new article configuration, returning to high viscosity (no flow at room temperature) and resistance to mechanical deformation indicating a crosslinked network. When the newly formed article of the reprocessable ethylene polymer composition is cooled to below the reprocessing temperature, the disulfide bonds in the reprocessable ethylene polymer composition are reestablished and the ethylene polymer (with BiTEMPS methacrylate) becomes a recrosslinked ethylene polymer composition in the shape of the newly manufactured article. Below the reprocessing temperature, the network disulfide bonds are stable and the recrosslinked ethylene polymer composition exhibits high viscosity and resistance to mechanical deformation indicative of the crosslinked network. This cycle of crosslinking / reprocessing / recrosslinking and manufacturing into new articles can be repeated.
[0116] Without being bound by a particular theory, the number of "reprocessing" cycles possible for the crosslinked ethylene compositions of the present invention (before competing thermal and oxidative permanent crosslinking occurs and prevents further reprocessing) can be determined by calculating the ratio of the melt viscosities of the crosslinked ethylene polymer composition before and after the reprocessing cycle. For the reprocessable, crosslinked ethylene polymer composition, the ratio of the Mooney viscosity after reprocessing to the Mooney viscosity before reprocessing is from 0.5 to 5, or from 0.7 to 3, or from 0.9 to 2, or from 0.95 to 1.2.
[0117] Other metrics used to monitor the number of "reprocessing" cycles possible for the BiTEMPS methacrylate dynamic crosslinker before competitive oxidative permanent crosslinking occurs include visual observation. The mechanically deformed formed film is heated to the reprocessing temperature and visually inspected to determine if the mechanically deformed film has healed to form a stable film. This measure of reprocessability is recorded in Table 2 below.
[0118] The present disclosure provides a method. In one embodiment, the method comprises:
[0119] The first article is heated to a reprocessing temperature. The first article is composed of a crosslinked ethylene polymer composition, the crosslinked ethylene polymer composition comprising (i) an ethylene polymer; and (ii) 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS methacrylate). The method includes forming the first article into a reprocessable ethylene polymer composition at a reprocessing temperature. The method includes forming the reprocessable ethylene composition into a reprocessed preform at a reprocessing temperature. The method includes cooling the reprocessed preform to below the reprocessing temperature and forming a second article composed of a recrosslinked ethylene polymer composition, the recrosslinked ethylene polymer composition consisting of (i) an ethylene polymer and (ii) BiTEMPS methacrylate, the second article being different from the first article.
[0120] In one embodiment, the forming step is a procedure selected from the group consisting of injection molding, extrusion molding, thermoforming, blow molding, overmolding, insert molding, blow molding, casting, tentering, compression molding, and combinations thereof.
[0121] Non-limiting examples of suitable articles (first article and second article) for the cross-linked / re-cross-linked ethylene polymer (with BiTEMPS methacrylate) composition of the present invention include elastic films; elastic fibers; soft-touch items such as toothbrush handles and appliance handles; pads and profiles; adhesives (including hot melt adhesives and pressure sensitive adhesives); footwear (including soles and shoe insoles); automotive interior parts and profiles; foam articles (both open-cell foams and closed-cell foams); impact modifiers for other thermoplastic polymers such as high-density polyethylene, isotactic polypropylene or other olefin polymers; coated fabrics; hoses; pipes; weather strips; lid linings; flooring; and combinations thereof.
[0122] By way of example and not limitation, some embodiments of the present disclosure will now be described in detail in the following examples.
[0123] 1. Materials
[0124] The materials used in the comparative samples (CS) and the inventive examples (IE) are provided in Table 1 below.
[0125] Table 1
[0126]
[0127] 1. Synthesis of BiTEMPS Methacrylate
[0128] To synthesize BiTEMPS methacrylate, 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide (8.78 g, 39.0 mmol, provided by TCI America) was first dissolved in anhydrous petroleum ether (about 90 mL, provided by Sigma-Aldrich, dried over molecular sieves for 48 hours before use) and cooled to -70 °C in a dry ice / acetone bath. Afterwards, sulfur monochloride (1.30 g, 9.7 mmol, provided by Sigma-Aldrich) was dissolved in anhydrous petroleum ether (about 1.25 mL) and added dropwise to the reaction vessel over a 30-minute period. The solution was stirred at -70 °C for another 30 minutes and at room temperature for 15 minutes. Next, BiTEMPS methacrylate was precipitated by pouring the reaction solution into a large amount of distilled water and stirring at room temperature overnight. The precipitate was collected, vacuum filtered, and vacuum dried at 60 °C for 48 hours to obtain BiTEMPS methacrylate as shown in the following structure 1.
[0129] Structure 1
[0130]
[0131] 2. Preparation of cross-linked composition
[0132] Appropriate masses of starting materials (including polymer pellets (ethylene polymer), crosslinker (BiTEMPS methacrylate) and free radical initiator (DCP)) were weighed separately on an analytical balance (usually 2 g polymer, 0.1 g crosslinker and 0.02 g free radical initiator). Prior to synthesis, the cup of a Dynisco (formerly Atlas) laboratory mixing molder (LMM) was charged with the target polymer, heated to above its melt transition temperature, and mixed for 3-5 minutes to rinse out impurities. After removing polymer debris from the rinse, the weighed polymer pellets and the powder mixture of the crosslinker and free radical initiator were added to the cup with a spatula. The starting materials were added in a certain amount so that they were evenly distributed throughout the cup before mixing. In addition, three steel balls (diameter ~5 mm) were evenly added to the cup to simulate the extrusion process during molten state mixing. Next, the temperature of the LMM is raised to above the melting transition temperature of the polymer, and the starting material is mixed at this temperature at 120rpm (maximum rotation speed) for 3 minutes to 5 minutes to ensure homogenization of the components in the molten state while minimizing free radical initiation. For polymers 4-6, the mixing temperature is 100°C. For polymers 2 and 7-10, the mixing temperature is 130°C. For polymer 1, the mixing temperature is 140°C. After this homogenization, the temperature of the LMM is raised to 160°C to start the free radical initiation and crosslinker grafting process. Mix at this temperature for about 20 minutes. During mixing, the rotor of the LMM is manually cycled up and down regularly to promote homogenization of the blend. After mixing for 20 minutes, the mixing is stopped and the crosslinked polymer blend is removed from the cup by a spatula.
[0133] The cross-linked composition (network blend) was cut into pieces and compression molded in a PHI press (model 0230C-X1) at 160°C and 8MPa for 30 minutes to form a film having a size of 50 mm long, 25 mm wide and 0.65 mm thick to obtain a first molded sample. The film was cut into millimeter-sized pieces and compression molded under the same conditions to obtain a second molded sample, and this procedure was repeated again to obtain a third molded sample. Strips were cut from each sample film for dynamic mechanical analysis (DMA).
[0134] 3. Polymer 7 (INFUSE TM 9100)
[0135] Select polymer 7 (INFUSE TM 9100), thermal property recovery was demonstrated by collecting DSC data after each consecutive compression molding cycle (up to three times) (Table 4). A 10°C / min heating rate and a -40°C / min cooling rate were applied for all measurements in the temperature range of -60°C to 160°C.
[0136] Polymer 7 (INFUSE TM The processability of the crosslinked compositions (network blends) of 9100) was evaluated by film quality after completing the standard compression molding procedure described above and the conditions in Table 2 (below). Polymer 7 (INFUSE TM 9100) cross-linked compositions (network blends) to evaluate the thermomechanical properties of the cross-linked compositions (network blends) compared to the native polymer 7 (INFUSE TM The network response of the first molded sample was compared to the 9100) material. Therefore, the performance criteria were based on the properties of the original polymer 7.
[0137] Table 2—Polymer 7 (INFUSE TM 9100)
[0138]
[0139] For processability, 1 - the network blend is not processable; the sheet will not heal to form a cohesive film for property testing. 2 - the network blend is partially processable; the sheet partially heals and requires more time to heal completely. The resulting film is intact and can be tested for properties.
[0140] 3-Network blends are fully processable; sheets are fully healed, allowing for exhaustive characterization testing and recycling.
[0141] N / A - Samples were not tested due to lack of processability (CS3-4, CS6-9) or network response (CS2).
[0142] Table 2 (above) shows the TM Inventive Examples (IE) and Comparative Samples of Crosslinkable Compositions of 9100) with Different Amounts of BiTEMPS Methacrylate ("BiT", Crosslinking Agent) and Different Amounts of Dicumyl Peroxide ("DCP", Free Radical Initiator). The crosslinkable compositions in Table 2 were mixed in a laboratory mixing molder (LMM) as described above to form crosslinked compositions. Each crosslinked composition sample was then cut into pieces, each piece being 50 mm long, 25 mm wide and 0.65 mm thick, and compression molded in a PHI press (Model 0230C-X1) at 160° C. and 8 MPa for 30 minutes to form a mm thick film to obtain a first molded sample.
[0143] The properties of each cross-linked film sample are shown in Table 2 as "Tested Properties". In Table 2, the minimum E' of 0.1 MPa at 140°C indicates that the network response (crosslinking) exceeds the thermoplastic response of the original polymer 7 (formulation CS1) containing a crosslinker and a free radical initiator. In general, for most polymers using 5 wt% crosslinker and 1 wt% free radical initiator, the synthesis of dynamic networks by the described procedure is successful. Table 2 shows (i) changing the amount of free radical initiator while keeping the amount of BiT crosslinker constant at 5 wt% crosslinker. Table 2 also shows (ii) changing the amount of BiT crosslinker while keeping the amount of free radical initiator constant at 1 wt%. This two-pronged approach enables the evaluation of the limits of achieving the network response (crosslinking) of the model polymer (in this case, polymer 7) while maintaining the processability of the compression molding machine.
[0144] From Table 2, the feasible ranges of crosslinker (BiT) and free radical initiator (DCP) for polymer 7 are 3 wt% to 20 wt% and 0.5 wt% to 1.25 wt%, respectively, relative to the loading mass of polymer 7. These ranges give a network response (crosslinking) above 0.1 MPa at 140°C and enable partial or full processability to be assessed by film quality after compression molding. In Table 2, crosslinked compositions IE1, IE3, IE4, IE5 and IE6 are fully processable (processability / film quality score of 3). IE1 (5 wt% crosslinker and 1 wt% free radical initiator, relative to 2 g of polymer 7 loading mass) produces an E' value of 0.992 at 140°C, associated with a strong dynamic network response. Comparative samples CS1-CS9 in Table 2 either did not produce network materials due to insufficient crosslinking agent or free radical initiator (CS1-2, 5), or could not be processed after compression molding due to overloading of free radical initiator, forming permanent crosslinks that could not undergo dynamic chemical reactions (CS3-4, 6-9). TM 9100) materials either flow above the melting transition temperature or fail to produce a healed film, both of which prevent characterization by DMA.
[0145] In addition, polymer 7 (INFUSE TM 9100) IE1 formulation was used to evaluate the minimum compression molding time required for processing at 160°C and 8 MPa, as shown in Table 3 below.
[0146] Table 3: Test polymer 7 (INFUSE TM 9100) processing time
[0147]
[0148] Performance Standard>1
[0149] Table 3 (above) shows that 25 minutes is part of the time required to process polymer 7 (INFUSE TM 9100) IE1 formulation, and 30 minutes is the minimum amount of time required to fully process this formulation under the same conditions. This confirms the standard processing procedures for other polymers, including a press time of 30 minutes.
[0150] Table 4 (below) shows the polymer 7 (INFUSE TM Thermal properties of IE1 of polymer 7 (9100) were obtained, including as-synthesized material and three consecutive molding cycles tested by DSC to demonstrate their thermal property recovery. Relative to the as-synthesized network, IE1 of polymer 7 recovered its values of crystallinity and melting temperature range upon recycling.
[0151] Table 4: Polymer 7 (INFUSE TM Relationship between thermal property recovery and processing cycle of IE1 formula of 9100
[0152] Table 4
[0153]
[0154] As shown in Table 4 above, IE1 of polymer 7 regains its values of crystallinity and melting temperature range upon recycling relative to the as-synthesized network.
[0155] 4. Polymer 1-10
[0156] Based on polymer 7 (INFUSE TM Based on the findings of the present invention (Figure 9100), the IE1 formulation of polymer 7 (2 g polymer base, 5 wt% crosslinker, 1 wt% free radical initiator) was converted to polymers 1-6 and 8-10. For polymers 1-6 and 8-10, sufficient network response and full recovery of the thermomechanical properties evaluated by DMA were obtained after 3 consecutive compression molding cycles using this formulation.
[0157] Table 5 is provided below.
[0158]
[0159] Table 5 shows E' and tan δ at 60°C and 140°C for the IE1 formulations of polymers 1-10. At 60°C, the E' values for the network polymers are equal (of the same order of magnitude) to the E' values for the corresponding virgin polymers within experimental uncertainty. Dynamic crosslinking and changes in crystallinity after processing may result in slightly reduced (reduced crystallinity reduces E' to below the melt transition temperature despite enhanced crosslinking) or slightly increased (crystallinity is slightly affected and crosslinking enhances E') E' values at this temperature compared to the virgin polymer. Sequential moldings for each IE1 polymer formulation exhibited E' values that were approximately equal (of the same order of magnitude) to the E' values for the corresponding virgin polymer and the first molded sample within experimental uncertainty at this temperature.
[0160] At 140°C, the E' values for the crosslinked compositions of network polymers IE1-IE10 were greater than the E' values for the corresponding virgin polymers 1-10 because virgin polymers 1-10 did not possess the network properties that would produce large E' values (>0.1 MPa) above the melt transition temperature. At 140°C, successive moldings of each of the crosslinked compositions of IE1-10 polymers exhibited E' values that were approximately equal (same order of magnitude) or slightly greater (due to additional crosslinks formed during processing) than the E' value of the first molded sample within experimental uncertainty.
[0161] The tan delta values of the IE1-10 crosslinked compositions (network formulations) at both 60°C and 140°C were lower than those of the corresponding native counterparts, polymers 1-10, due to the presence of greater crosslinking in the network material. In addition, these values were maintained in samples molded continuously at both 60°C and 140°C. The IE1-10 crosslinked compositions shown in Table 5 demonstrate that polymers 1-10 not only exhibited a significant dynamic network response after crosslinking (>1 MPa at 60°C and >0.1 MPa at 140°C), but also were reprocessable and were able to recover their E' and tan delta values after consecutive compression molding cycles. The comparative samples that were processable failed to achieve a significant network response, while those that were able to produce a significant network response could not be reprocessed and were unable to recover thermomechanical properties after processing due to the presence of permanent crosslinks rather than sufficient dynamic crosslinks.
[0162] Table 5 provides the thermal properties (melting range and crystallinity) of virgin polymers 1-10 (comparative samples) and crosslinked compositions of inventive examples IE1-10 (network formulations) as determined by DSC. Reactive crosslinking reduces the order of the formed crystalline structure during cooling after processing, slightly reduces crystallinity, and reduces the melting peak and endpoint of the network polymers compared to the virgin counterparts polymers 1-10 (comparative samples).
[0163] Table 6 below shows the thermal creep data for the following materials: (i) Original INFUSE TM 9100 ethylene / octene multi-block copolymer (comparative sample), (ii) a crosslinked ethylene polymer composition (IE7-1) composed of 5 wt% BiTEMPS methacrylate, (iii) a native ENGAGE TM 8003 ethylene / octene random copolymer (comparative sample) and (iv) prepared by ENGAGE TM 8003. A crosslinked ethylene composition (IE4-1) composed of ethylene / octene random copolymer and 5 wt% BiTEMPS methacrylate.
[0164] Table 6
[0165]
[0166] It is particularly intended that the present disclosure is not limited to the embodiments and descriptions contained herein, but includes modifications of those embodiments including parts of the embodiments and combinations of elements of different embodiments as appear within the scope of the following claims.
Claims
1. A crosslinkable polymer composition, comprising: Ethylene polymers; free radical initiators; and 2,2,6,6-Tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS methacrylate). 2 . The crosslinkable polymer composition according to claim 1 , wherein the melt index of the ethylene-based polymer is from 0.1 g / 10 min to 100 g / 10 min.
3. The crosslinkable polymer composition according to any one of claims 1 to 2, wherein the ethylene-based polymer is selected from the group consisting of ethylene plastomers / elastomers, high density polyethylene (HDPE), linear low density polyethylene (LLDPE), low density polyethylene (LDPE), ethylene / α-olefin multi-block copolymers and combinations thereof.
4. The crosslinkable polymer composition according to any one of claims 1 to 3, wherein the free radical initiator is an organic peroxide.
5. The crosslinkable polymer composition according to any one of claims 1 to 4, comprising: 70 wt % to 98.5 wt % of said ethylene polymer; 0.5 wt % to 10.0 wt % of a free radical initiator; and 1 wt % to 20 wt % BiTEMPS methacrylate.
6. The crosslinkable polymer according to any one of claims 1 to 5, wherein the free radical initiator is dicumyl peroxide.
7. A cross-linked composition, comprising: Ethylene polymers; and 2,2,6,6-Tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS methacrylate).
8. The cross-linked composition according to claim 7, wherein the cross-linked composition comprises a bond of structure 2 9. The cross-linked composition according to any one of claims 7 to 8, comprising: 80 to 99 weight percent of an ethylene-based polymer having a melt index of 0.1 to 100 g / 10 min; and 20 wt % to 1 wt % of said BiTEMPS methacrylate.
10. The crosslinked composition according to any one of claims 7 to 9, wherein the ethylene-based polymer is selected from the group consisting of ethylene plastomers / elastomers, high density polyethylene (HDPE), linear low density polyethylene (LLDPE), low density polyethylene (LDPE), ethylene / α-olefin multi-block copolymers, and combinations thereof.
11. The cross-linked composition according to any one of claims 7 to 10, wherein The ethylene polymer is a virgin ethylene polymer prior to crosslinking the crosslinking composition; and The cross-linked composition has (i) a storage modulus value E' at 140°C, which is greater than the storage modulus value E' of the native ethylene polymer at 140°C; (ii) a tan δ value at 60°C that is less than the tan δ value at 60°C of the native ethylene polymer; and (iii) a tan δ value at 140°C that is less than the tan δ value of the native ethylene polymer at 140°C.
12. The cross-linked composition according to any one of claims 7 to 11, comprising: 3 wt % to 20 wt % BiTEMPS methacrylate; and The cross-linked composition has (i) a storage modulus value E' greater than 1 MPa at 60°C; (ii) a storage modulus value E' at 140°C greater than 0.1 MPa; (iii) a tan delta value of less than 0.17 at 60°C; and (iv) a tan δ value of less than 0.62 at 140°C.
13. A method comprising: heating a first article to a reprocessing temperature, the first article being comprised of a crosslinked ethylene polymer composition comprising (i) an ethylene polymer; and (ii) 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS methacrylate); forming the first article into a reprocessable ethylene polymer composition at the reprocessing temperature; forming the reprocessable ethylene composition into a reprocessable preform at the reprocessing temperature; as well as The reprocessed preform is cooled to below the reprocessing temperature and forms a second article composed of a recrosslinked ethylene polymer composition, wherein the recrosslinked ethylene polymer composition is composed of (i) the ethylene polymer and (ii) the BiTEMPS methacrylate, and the second article is different from the first article.
Citation Information
Cited By
Preparation method and application of dynamically and reversibly crosslinked high-absorptivity resin
CN121800985A